Management of research and scientific production in private universities of metropolitan Lima - Olivera Roque, Roxana Haydeé (2022)
A documentary review was carried out on the production and publication of research papers referring to the study of the variable Scientific Production in Latin American universities, in order to compare research management with private universities in Lima, Peru. The purpose of the bibliometric analysis proposed in this document is to know the main characteristics of the volume of publications registered in Scopus database during the period between 2016 and 2021, achieving the identification of 546 publications. The information provided by said platform was organized by means of graphs and figures categorizing the information by Year of Publication, Country of Origin, Area of Knowledge and Type of Publication. Once these characteristics were described, the position of different authors regarding the proposed topic was referenced by means of a qualitative analysis. Among the main findings of this research, it is found that Brazil is the country with the highest production with 243 publications. The Area of Knowledge that made the greatest contribution to the construction of bibliographic material referring to the study of research management and Scientific Production in Latin American Universities was Social Sciences with 318 published documents, and the Type of Publication that was most used during the above-mentioned period was the Journal Article, which represents 77% of the total scientific production.